2022
DOI: 10.1002/prot.26317
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the SARS‐CoV‐2 envelope protein monomer

Abstract: Coronaviruses, especially severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), present an ongoing threat to human wellbeing. Consequently, elucidation of molecular determinants of their function and interaction with the host is an important task. Whereas some of the coronaviral proteins are extensively characterized, others remain understudied. Here, we use molecular dynamics simulations to analyze the structure and dynamics of the SARS‐CoV‐2 envelope (E) protein (a viroporin) in the monomeric form. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 143 publications
(241 reference statements)
3
36
0
Order By: Relevance
“…SARS-CoV-2 evolution has been extensively studied by computational approaches [44,[57][58][59][60][61][62]. Our retrospective analysis of SARS-CoV-2 variants revealed an early divergence between conserved (ADE) and variable (neutralizing) epitopes which is based on their localization on the spike protein.…”
Section: Discussionmentioning
confidence: 95%
“…SARS-CoV-2 evolution has been extensively studied by computational approaches [44,[57][58][59][60][61][62]. Our retrospective analysis of SARS-CoV-2 variants revealed an early divergence between conserved (ADE) and variable (neutralizing) epitopes which is based on their localization on the spike protein.…”
Section: Discussionmentioning
confidence: 95%
“…Over the course of the COVID-19 pandemic, the SARS-CoV-2 spike (S) protein has incurred many mutations [81][82][83][84][85], raising the concern that other viral proteins might also have incurred mutations. However, several studies have analyzed sequenced genomes obtained from COVID-19 databases and reported minimal mutations in the SARS-CoV-2 E gene [85][86][87][88][89][90][91], remarking that the E protein and its properties are highly conserved [90][91][92][93][94]. We therefore conclude that the full-length, 3D structures predicted for all five of the E proteins successfully passed quality assessment, and based on the low RSMD values, we are confident that the correct protein folds were assigned to the respective protein sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also modelled hCoV E proteins, but they have focused exclusively on the more virulent hCoV E proteins and excluded the less virulent ones [36,92,93,95]. Some studies have only constructed partial models of SARS-CoV-2 E using 5X29 as template [95] or SARS-CoV-1, -2, and MERS-CoV E proteins from the 2MM4 template [92].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other attempts against MPro were done [ 130 , 131 , 132 , 133 ] but require further experimental data to validate the hypothesis. The RNA polymerase, [ 134 ] as well as the nucleocapsid, [ 135 ] and envelope protein [ 136 ] were proposed as a druggable target, but these studies will require further confirmation by experimental data to verify whether NSPs could be considered viable targets.…”
Section: Molecular Dynamics Insights On New Sars‐cov‐2 Variantsmentioning
confidence: 99%